Fostering social acceptance of students with developmental difficulties in vocational secondary school classes - Vujačić Milja; Đević Rajka (Nastava i Vaspitanje, 2025)
The aim of the study is to examine the practices that teachers use for encouraging social acceptance of students in the context of inclusive education. Fifty teachers from seven vocational high schools of various profiles in Serbia were asked to participate in a questionnaire in which they described the ways they encourage the social acceptance of students with developmental difficulties. Data processing was conducted through qualitative thematic content analysis, focusing on the following themes: the teachers' positive attitudes toward students with developmental difficulties, support in the learning process, and the sensitisation of students. The findings indicate that the teachers recognise the importance of the social component of inclusive education, that their practices align with the key principles of this process, and that they succeed in finding solutions to the various challenges posed by inclusive teaching in order to achieve the intended outcomes. They nurture positive relationships with their students by unlocking their latent potential, creating opportunities for learning and progress, and demonstrating a willingness to engage in professional development and collaboration. The teachers pay attention to student sensitisation through the development of social skills and the encouragement of prosocial behaviour. They apply cooperative learning, individualisation, and various motivational strategies in their teaching practice so as to stimulate cognitive progress and the social acceptance of individuals. This study suggests that it would be advisable for schools and the educational system as a whole to encourage teachers to regularly share their experiences and tried-and-tested solutions in the inclusive education process through various forms of professional development, such as collaborative learning and cooperation. Future research in this field should involve a larger number of teachers, apply other qualitative methods such as interviews, focus groups and systematic observation and include diverse stakeholders in order to gain a more comprehensive insight into teaching practices.